Cross-cultural validity of the Death Reflection Scale during the COVID-19 pandemic - Ramsenthaler, Christina; Baumann, Klaus; Büssing, Arndt; Becker, Gerhild (Frontiers in Psychology, 2022)
Background: The global COVID-19 pandemic confronts people with their fragility, vulnerability and mortality. To date, scales to measure death awareness mainly focus on the anxiety-provoking aspect of mortality cues. This study aims to cross-culturally adapt and validate the Death Reflection Scale (DRS), a scale for measuring positive, growth-oriented cognitions of life reflection and prosocial behavior following confrontation with the finiteness of life. Method: The Death Reflection Scale was translated and adapted in a multi-step process to the German language. In this anonymous, cross-sectional, online survey at a large university in Germany, students, healthcare professionals (HCP) and other staff completed the DRS alongside comparison measures. Multi-group confirmatory factor analysis was used to assess configural, metric, and scalar measurement equivalence across four age and occupational groups. Convergent/divergent validity testing was done via Spearman correlations. Results: 1,703 participants provided data for a response rate of ~5%. 24% of respondents were HCP, 22% students. Confirmatory factor analysis showed a higher-order bifactor structure of the DRS with a strong general factor and the originally proposed five subscales (CFI .945, SRMR .045, RMSEA .055). Multi-group CFA showed partial metric equivalence across age groups and partial scalar invariance across occupational groups. Non-invariant scales were the Motivation to live, Putting life into perspective, and Legacy subscales. In the convergent validity testing, two hypotheses were fully confirmed, two partially and four were not confirmed. Experiencing a propensity for increased contemplation and life reflection during the pandemic together with spirituality showed correlations of moderate to large size to the DRS and its subscales (Spearman’s rho ranging from .31 to .52). Conclusions: Further conceptual work for death awareness to explore the construct’s stability in different population groups needs to be undertaken. However, the DRS can be mostly used to assess positive and growth-oriented aspects of death awareness and death reflection which may be an important avenue when developing counselling and support interventions for groups experiencing a high burden during the pandemic.